2016
DOI: 10.1002/jor.23274
|View full text |Cite
|
Sign up to set email alerts
|

Factors regulating bone remodeling processes in aseptic implant loosening

Abstract: This study was undertaken to screen periprosthetic tissues (PPTs) under specified conditions for a series of molecular components and describe them in bone remodeling processes within aseptic loosening. PPT samples were obtained from patients undergoing revision surgery of endoprostheses (n = 24) and synovial tissues from patients with OA (control) (n = 18), patients with any form of inflammatory arthritides were excluded. Tissue samples were examined via microbiology, histology (H&E, TRAP), immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…It showed a more pro-osteoclastogenic environment in all transwell cultures, independent of cell type. These findings match our previous results, where periprosthetic tissue (from which PPFs were isolated) was analyzed [ 25 ]. The multilayer aggregates seem to present an interesting approach to analyze fibroblasts within a cell-culture system mimicking in vivo situations more closely.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It showed a more pro-osteoclastogenic environment in all transwell cultures, independent of cell type. These findings match our previous results, where periprosthetic tissue (from which PPFs were isolated) was analyzed [ 25 ]. The multilayer aggregates seem to present an interesting approach to analyze fibroblasts within a cell-culture system mimicking in vivo situations more closely.…”
Section: Discussionsupporting
confidence: 91%
“…There is lots of evidence that the function of fibroblast-like cells is far beyond creating a supporting tissue. Expression of RANKL, the final effector of osteoclastogenesis and bone resorption, has been shown to be increased in periprosthetic tissues [ 25 ]. It has been demonstrated that prostaglandin E2 (PGE2) signaling upregulates RANKL expression in PPFs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wear debris particles typically stimulate osteoclast proliferation and differentiation by activating the OPG/RANKL/RANK pathway [ 30 ]. Hartmann et al [ 31 ] examined the mRNA expression of RANK and OPG and the binding activity of NF- κ B by coculturing titanium particles with IC-21 macrophages. The results showed that the osteolytic reaction process could be initiated by titanium particles through the OPG/RANKL/RANK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…1 Successful bone remodeling in dental implants depends on the balanced activation of osteoclasts, which resorb the underlying bone tissue, followed by subsequent activation of osteoblasts, which are responsible for formation of new bone tissue in the peri-implant region. [2][3][4] Under osteoporotic conditions, estrogen deciency up-regulates osteoclastic activity, and this osteolysis phenomenon is further intensied. 5 Thereaer, it is desirable to nd useful interventions to promote the initial stability and long-term survival of implants, not only for the normal patients but also for the patients suffering from osteoporosis.…”
Section: Introductionmentioning
confidence: 99%